Beta-Tocotrienol Exhibits More Cytotoxic Effects than Gamma-Tocotrienol on Breast Cancer Cells by Promoting Apoptosis via a P53-Independent PI3-Kinase Dependent Pathway - Maya Idriss (Biomolecules, 2020)
Studies on tocotrienols have progressively revealed the benefits of these vitamin E isoforms on human health. Beta-tocotrienol (beta-T3) is known to be less available in nature compared to other vitamin E members, which may explain the restricted number of studies on beta-T3. In the present study, we aim to investigate the anti-proliferative effects and the pro-apoptotic mechanisms of beta-T3 on two human breast adenocarcinoma cell lines MDA-MB-231 and MCF7. To assess cell viability, both cell lines were incubated for 24 and 48 h, with different concentrations of beta-T3 and gamma-T3, the latter being a widely studied vitamin E isoform with potent anti-cancerous properties. Cell cycle progression and apoptosis induction upon treatment with various concentrations of the beta-T3 isoform were assessed. The effect of beta-T3 on the expression level of several apoptosis-related proteins p53, cytochrome C, cleaved-PARP-1, Bax, Bcl-2, and caspase-3, in addition to key cell survival proteins p-PI3K and p-GSK-3 α/β was determined using western blot analysis. Beta-tocotrienol exhibited a significantly more potent anti-proliferative effect than gamma-tocotrienol on both cell lines regardless of their hormonal receptor status. Beta-T3 induced a mild G1 arrest on both cell lines, and triggered a mitochondrial stress-mediated apoptotic response in MDA-MB-231 cells. Mechanistically, beta-T3′s anti-neoplastic activity involved the downregulation of phosphorylated PI3K and GSK-3 cell survival proteins. These findings suggest that vitamin E beta-T3 should be considered as a promising anti-cancer agent, more effective than gamma-T3 for treating human breast cancer and deserves to be further studied to investigate its effects in vitro and on other cancer types.